A study on quality culture at UMW Advantech Shah Alam / Khairul Muzzammil Idris - Idris, Khairul Muzzammil (Faculty of Business and Management, 2010)
Firstly, the aim of this study was to explore the relationship between top management commitment, training, and effective communication with the quality culture development. This research project was held at UMW Advantech Shah Alam where the company business focuses is auto parts manufacturing for automobile manufacturer such as Proton and Perodua. Basically there are ten factors or agent that become a catalyst towards quality culture development, for instances top management commitment, customer management, training, teamwork, people management and empowerment, supplier partnership, quality planning and strategic, process management, rewards and recognition, and effective communication. (Ahmed et al, 2005, Haupt and Whiteman, 2004, Rita, 2003). This thesis research only use three factors there are top management commitment, training, and effective communication because of some limitation. Furthermore, this research was done at plastic mold plant and the respondents are employees at quality assurance department, inventory department, research and development department, and the operators. There are only 71 questionnaires were distributed to the respondents and only 66 samples were returned. The result used the Statistical Package for Social Science (SPSS). The results proved that there are relationship between top management commitment, training, and effective communication with the quality culture development. Besides that in the chapter four will explain the finding analysis and interpretation in this study. This chapter comprises the reliability analysis, frequency analysis, means analysis, and Pearson’s correlation matrix.